The Lie Became Great : The Forgery of Ancient Near Eastern Cultures - Muscarella, (Studies in the art and archaeology of antiquity., 2002)
The Lie Became Great explores the closed society of international plunderers and forgers which thrives as a subculture of the Art World. These multi-cultural denizens include antiquity dealers, collectors, museum curators, forgers working in conjunction with auction houses, museums and galleries. Forgeries are made to be sold, and a great number pass into the Art World - collections, exhibitions, catalogues, and popular and scholarly journals - complete with their fabricated stories of excavation, and how they were found. The Lie Became Great documents the success and activities of one small corner of this vast network - artifacts form the Ancient Near East - with hundreds of detailed catalogue entries of forgeries. The participants in this society gain money, prestige, power, position as they distort and irretrievably damage the true story of our cultural heritage. STYX PUBLICATIONS.